The importance of symbolic and engaged participation in evidence-based quality improvement in a complex integrated healthcare system: response to “The science of stakeholder engagement in research” - Hamilton, Alison B. (Transl Behav Med, 2017)
In this commentary, we respond to the commentary provided by Goodman and Sanders Thompson regarding our paper on multilevel stakeholder engagement in a VA implementation trial of evidence-based quality improvement (EBQI) in women’s health primary care. We clarify our overall approach to engagement (comprised of both symbolic and engaged participation, according to the authors’ classification rubric), highlighting that symbolic participation is of more import and value than the authors suggest, especially in the context of a hierarchical healthcare system. We contend that the issue of power—and how power matters in stakeholder engagement—needs to be considered in this context rather than in global “community” terms. In response to the authors’ call for greater detail, we clarify our planning processes as well as our approach to veteran engagement. We concur with Goodman and Sanders Thompson that the science of stakeholder engagement necessitates a broader understanding of best practices as well as the impact of engagement on implementation outcomes.